Using comics and curiosity to drive pandemic research on a national scale. (2nd January 2021) - Kearns, Ciléin; Kearns, Nethmi; Braithwaite, Irene; Shortt, Nick; Eathorne, Allie; Semprini, Alex; Beasley, Richard
Abstract: An independent online Public Health survey regarding the COVID-19 pandemic was conducted during an Alert Level 4 lockdown, the highest possible, in New Zealand. An illustrated and curiosity-driven public engagement campaign was designed to advertise survey participation, and performance compared with a standard approach using randomised controlled A/B Split tests. The 'Caretoon' approach featured comic illustrations, appealed to goodwill and was intended to pique curiosity. This linked to an illustrated version of the survey which, upon completion, gave a personalised comic summary showing how respondent's answers compared with national averages. The standard ad and survey were not illustrated with comics, and did not provide a personalised comic summary on completion. Both approaches were cost- and time-effective, together resulting in 18, 788 responses over six days. The Caretoon approach outperformed the standard approach in terms of the number of people reached, engaged, survey link clicks, gender and ethnic diversity amongst respondents, and cost-effectiveness of advertising. This came at the expense of a small reduction in the proportion of completed surveys and male respondents. The research evidences objective value of public engagement activity, comics and curiosity as tools which can support Public Health research on a national scale.